Co-existent medial collateral ligament injury seen following transient patellar dislocation: observations at magnetic resonance imaging. Issue 6 (19th November 2008) - Quinlan, J F; Farrelly, C; Kelly, G; Eustace, S
Abstract : This study reports on a series of patients who were diagnosed as having had a transient lateral patellar dislocation by magnetic resonance imaging (MRI). The images were reviewed with specific reference to the medial collateral ligament (MCL), a heretofore undescribed concomitant injury. Eighty patients were diagnosed on MRI as having had transient lateral patellar dislocation. Their mean age was 23.9 years (SD 7.5). Forty patients (50.0%) had co-existent MCL injuries. These injuries were classified as grade 1 (n = 20), grade 2 (n = 17) and grade 3 (n = 3). These results suggest that MCL injury commonly accompanies transient lateral patella dislocation, most likely due to a shared valgus injury. It appears to occur more commonly in male patients and if unidentified may explain both delayed recovery and persistent morbidity in more severe cases. In this setting, without specifically excluding co-existent MCL injury, the current vogue for early rehabilitation should be adopted with caution.